Development of a standardized monoclonal antibody to the inner lipoyl domain of PDC-E2 as a potential international AMA reference - Zhuye Qin; Fangming Cheng; Mingming Zhang; Ruonan Qian; Hong Chen; Yaqin Zhao; Youtao Zhang; Yaping Dai; Chaochao Tang; Peng Jiang; Xiaoli Hua; Shen Li; et al. (Journal of Translational Autoimmunity)
The detection of antimitochondrial antibodies (AMA) is the specific diagnostic marker for primary biliary cholangitis. Indeed, it is the most specific autoantibody in clinical autoimmunity, with a high titer directed response to the inner lipoyl domain of PDC-E2. The current international reference for AMA detection is based upon sera samples of PBC patients. In rheumatic diseases, i.e. rheumatoid arthritis, great efforts are placed at development of international standards. In this study, we report the development of a monoclonal chimeric IgG1 antibody as a reference for AMA testing. A monoclonal 4G6 antibody was constructed from a murine monoclonal antibody specific for the inner lipoyl domain (ILD) of PDC-E2, by combining the variable region with the constant region of human IgG1. The 4G6 antibody recognizes all AMA epitopes containing the ILD of PDC-E2, including the classical BPO recombinant antigen in all currently available diagnostic methods. The binding affinity of the 4G6 antibody to PDC-E2 and BPO antigen reaches KD value of 7.22 × 10−11 M and 4.55 × 10−11 M, which is sufficient to use as a quantitative reference for all AMA tests. The unlimited availability of the 4G6 antibody makes it a promising candidate for use as an AMA reference or assay calibrator for the international community.